1996
DOI: 10.1038/nm1096-1136
|View full text |Cite
|
Sign up to set email alerts
|

Proliferation in the auditory receptor epithelium mediated by a cyclic AMP–dependent signaling pathway

Abstract: Loss of receptor hair cells in the cochlea accounts for a significant proportion of hearing impairment in the population. Hair cells can be lost as a consequence of viral or bacterial insult, aging, and damage from intense sound or aminoglycoside antibiotics. The generation of replacement hair cells following damage by sound or drugs has been clearly demonstrated in birds; the chick is the best-studied model for auditory hair cell regeneration. New hair cells arise as progeny from an otherwise nondividing supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(42 citation statements)
references
References 24 publications
1
40
1
Order By: Relevance
“…Subsequently, postmitotic cells differentiate into either HCs or SCs. Previous studies demonstrated that SCs from the chicken BP reenter the cell cycle in organ cultures (Oesterle et al 1993;Navaratnam et al 1996;Warchol and Corwin 1996) and in pure SC cultures (Stone et al 1996) following HC loss. In this study, the distribution of dividing SCs was different in streptomycin-treated cultures than in control cultures.…”
Section: Patterns Of Sc Proliferation Vary In Control and Streptomycimentioning
confidence: 96%
See 1 more Smart Citation
“…Subsequently, postmitotic cells differentiate into either HCs or SCs. Previous studies demonstrated that SCs from the chicken BP reenter the cell cycle in organ cultures (Oesterle et al 1993;Navaratnam et al 1996;Warchol and Corwin 1996) and in pure SC cultures (Stone et al 1996) following HC loss. In this study, the distribution of dividing SCs was different in streptomycin-treated cultures than in control cultures.…”
Section: Patterns Of Sc Proliferation Vary In Control and Streptomycimentioning
confidence: 96%
“…Oesterle et al (1993) also showed that limited SC division occurs in organ cultures maintained without ototoxic drugs for 2 days. Other studies showed that substantial SC division occurs in organ cultures after drug damage (Navaratnam et al 1996;Daudet et al 2009) or HC ablation (Warchol andCorwin 1996), with some mitotic events leading to production of new HCs (Navaratnam et al 1996). In the current study, we examined the time course, levels, and spatial patterns of SC division and HC regeneration in cultured chicken BPs treated with streptomycin.…”
Section: Introductionmentioning
confidence: 99%
“…FSK treatment induces supporting cell proliferation and ultimately the formation of replacement hair cells in the avian basilar papilla (Navaratnam et al 1996). Here, we determine the direct effects of FSK treatment in the basilar papilla by measuring the levels of cAMP after FSK treatments.…”
Section: Forskolin Treatment Induces Camp Accumulation In the Avian Bmentioning
confidence: 99%
“…In a previous study from our lab, we identified the cAMP/PKA pathway as the first signal transduction pathway in the formation of replacement hair cells in the avian auditory epithelium. We reported that treatment of undamaged cultured avian cochlear explants with several doses of the adenyl cyclase activator forskolin (FSK), or with cell-permeable cAMP analogs, induces DNA synthesis in auditory supporting cells and, after several days, results in the appearance of hair cells labeled with markers of DNA synthesis (Navaratnam et al 1996). Although supporting cell proliferation in the auditory epithelium can be mediated by FSK treatment, the cellular responses to FSK treatment in the basilar papilla and the downstream targets of the cAMP/PKA pathway have yet to be elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Aminoglycoside antibiotics, such as neomycin, selectively kill hair cells in cultures of the avian ear organs (Navaratnam et al, 1996;Stone et al, 1996;Hirose et al, 1997;Kil et al, 1997;Warchol, 1999;Matsui et al, 2000a). To characterize the pattern of hair cell loss induced by neomycin, we incubated utricles in control (aminoglycoside-free) medium for 24 hr and then in 1 mM neomycin-supplemented medium for another 24 hr.…”
Section: Changes In Cell Survival and Nuclear Chromatin After Neomycimentioning
confidence: 99%